2008
DOI: 10.2298/aoo0804039b
|View full text |Cite
|
Sign up to set email alerts
|

Activity of lactate dehydrogenase and superoxide dismutase in the circulation of patients with breast carcinoma

Abstract: Background: A rapid increase in the turnover of malignant cells modulates the enzymes level in circulation and may be a prognostic sign of disease progression. We evaluated the activity of serum lactate dehydrogenase and superoxide dismutase in erythrocytes of breast cancer patients immediately after surgery and before adjuvant therapy. Methods: Fourteen newly operated breast cancer patients were included in the study. Lactate dehydrogenase and superoxide dismutase activity were estimated using standard tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Studies have shown that SOD activity was augmented in the early stages of the disease; therefore, it can be used as a marker for the diagnosis of breast cancer (Bogdanović et al, 2008).…”
Section: Oxidative Stress and Breast Cancermentioning
confidence: 99%
“…Studies have shown that SOD activity was augmented in the early stages of the disease; therefore, it can be used as a marker for the diagnosis of breast cancer (Bogdanović et al, 2008).…”
Section: Oxidative Stress and Breast Cancermentioning
confidence: 99%
“…Nearly 50% of BC patients will develop distant metastasis, and at some point, more than half patients with metastatic BC will have liver involvement [6]. An increased rate of metabolic changes like anaerobic glycolysis and oxidative stress results in a rapid turnover of cancer cells that modulates the enzyme level in blood circulation [7].…”
Section: Introductionmentioning
confidence: 99%
“…LDH activity correlates with tumor burden, and the metastatic BC exhibits elevated LDH level than normal breast tissue [7]. Gamma Glutamyl transpeptidase (GGT) is an enzyme of glutathione metabolism, involved in cell's detoxification pathway and apoptotic balance-including tumor development, progression and chemotherapy resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(13) Reported that patient of early carcinoma breast had normal values of Serum Lactate dehydrogenase and only in one patient of stage III b the value of Lactate dehydrogenase was raised by 2 folds. The mean LDH was 6.73 ukat/L (402.99 IU/L) in his study which nearby correlates to our present study in which the mean LDH in early stage is 482.75 IU/L.…”
Section: Resultsmentioning
confidence: 99%